Business Feasibility Analysis of Processed Chicken Feet Products "Dakbal Bali" - Putu Diah Wahyuni; Ni Made Ayu Suardani Singapurwa (Jurnal Multidisiplin Madani, 2023)
Chicken feet are a by-product waste from chicken slaughterhouses with very limited utilization. Therefore, a solution is needed in overcoming chicken feet waste into a product with economic value.  The utilization of chicken feet can be processed into soup, chicken noodles and chips.  Protein content in chicken feet is used as gelatin in addition, chicken feet bones is also processed into flour which contains nutrients, especially calcium.   Chicken is processed into products in entrepreneurial activities by one of the students of the Food Science and Technology study program at Warmadewa University. The name of this processed claw product is "Spicy and Chevy Boneless Chewy". The spicy and chewy boneless claw processed product has a name, namely "DAKBAL BALI".  The advantages of this product are that consumers are more practical, not messy in consuming feet and the time needed is also shorter and more efficient. The target of selling processed food products per week is 25 packs. The selling time for spicy and chewy boneless feet products is Monday-Sunday, which means that in a month sell 100 packets of spicy and chewy boneless feet (20 kg), spicy and chewy     boneless feet. The Break Even Point of this product is 88 packs with a total cost of 1,311,609